Is Embodiment All That We Need? Insights from the Acquisition of Negation - Valentina Cuccio (Biolinguistics, 2012)
Simulation of propositional content does not sufficiently explain real-life linguistic activity, even for action-related language. In addition, how we get from propositional content to implicit and inferential meaning needs to be explained. Indeed, simulative understanding is immediate, automatic and reflex-like while an explicit interpretative act, even if not always needed, is still a part of many linguistic activities. The aim of this paper is to present the hypothesis that speaking is a complex ability realized by means of at least two different mechanisms that are likely developed at different and consecutive steps of cognitive and linguistic development. The first mechanism has a neural explanation grounded in the notion of embodied simulation. The second implies socio-cognitive skills such as Theory of Mind. In order to fully develop the second mechanism, a symbolic communication and interaction with a cultural community are needed. This hypothesis will be tested by looking at the acquisition of linguistic negation.